Enhancing hydrogen storage performance of magnesium hydride through doping with nanosized aluminum catalyst produced by electrical explosion of wires technique: Part 1 – Hydrogen sorption/desorption kinetics and Ab initio studies - Kenzhiyev A. Alan; Kudiyarov V. N. Victor Nikolaevich; Kurdyumov N. Nikita; Elman R. R. Roman Romanovich; Terentjeva D. V. Darjya Vitaljevna; Svyatkin L. A. Leonid Aleksandrovich (2026, 2026)
Title screen